A Methodology for the Optimized Design of an E/E Architecture Component Platform - Graf, Sebastian; Glaß, Michael; Teich, Jürgen; Platte, Daniel (Proceedings of the Stuttgart International Symposium, 2015)

Analyzing Automotive Networks using Virtual Prototypes - Graf, Sebastian; Streubühr, Martin; Glaß, Michael; Teich, Jürgen (Proceedings of the Automotive meets Electronics (AmE2011), GMM Fachbericht 69, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.inform.analyz

Considering MOST150 during Virtual Prototyping of Automotive E/E Architectures - Graf, Sebastian; Russ, Thomas; Glaß, Michael; Teich, Jürgen (Proc. of Automotive meets Electronics (AmE), GMM Fachbericht 72, 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.inform.consid

Design and Evaluation of Future Ethernet AVB-based ECU Networks - Glaß, Michael; Graf, Sebastian; Reimann, Felix; Teich, Jürgen (Embedded Systems Development, From Functional Models to Implementations 2014, 2014)
UnivIS-Import:2015-04-20:Pub.2013.tech.IMMD.inform.design

Design and Optimization of Multi-Variant Automotive E/E Architecture Component Platforms - Graf, Sebastian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)

Design Space Exploration for Automotive E/E Architecture Component Platforms - Graf, Sebastian; Glaß, Michael; Teich, Jürgen; Lauer, Christoph (Proc. of Euromicro Conference on Digital System Design (DSD), 2014)
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.inform.design

Exploration of Power Domain Partitioning for Application-Specific SoCs in System-Level Design - Wang, Bo; Xu, Yang; Hasholzner, Ralph; Drewes, Christian; Rosales, Rafael; Graf, Sebastian; Falk, Joachim; Glaß, Michael; Teich, Jürgen (In Proceedings of the 19. GI/ITG/GMM-Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2016), 2016)

Investigating the Impact of Energy-Efficient Ethernet on Automotive Applications via High-level Modeling - Graf, Sebastian; Glaß, Michael; Teich, Jürgen (Tagungsunterlagen Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.inform.invest

IVaM: Implicit Variant Modeling and Management for Automotive Embedded Systems - Graf, Sebastian; Glaß, Michael; Wintermann, Dominic; Teich, Jürgen; Lauer, Christoph (Proc. International Conference on Hardware/Software Codesign and System Synthesis, 2013)
In this paper, we propose a graph-based approach for the modeling and efficient analysis of functional variants of a car's electric and electronic (E/E) architecture functionality by combining local technical expert knowledge with global business knowledge. Starting with a variants system specification including a set of task graphs, linear constraints on binary variables are specified for their alternative selection as well as the selection of groups of alternatives called application groups. These constraints may stem from a certain domain knowledge, e. g., entertainment or power train domain, or global constraints. The typically vast space of resulting possible combinations of different selections of alternative behaviors will be termed variant space and those satisfying the set of formulated constraints valid variants. An important result of this paper is that the set of variants, and especially the set of valid variants, do not need to be modeled or stored explicitly but rather implicitly. Nevertheless do we show that using state-of-the-art PB solver techniques, we may determine the set of valid variants very efficiently. Each of these valid variants may subsequently be used as a candidate for design space exploration (DSE) in order to optimize also the mapping of the corresponding task graph functionalities to a final optimized E/E architecture. A real-world case study is provided to demonstrate the capabilities and efficiency of the presented approach on implicit variant modeling and analysis. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.inform.ivamim

Multi-Variant-based Design Space Exploration for Automotive Embedded Systems - Graf, Sebastian; Glaß, Michael; Teich, Jürgen; Lauer, Christoph (Proc. of Design, Automation and Test in Europe (DATE), 2014)
This paper proposes a novel design method for modern automotive electrical and electronic (E/E) architecture component platforms. The addressed challenge is to derive an optimized component platform termed Baukasten where components, i. e., different manifestations of Electronic Control Units (ECUs), are reused across different car configurations, models, or even OEM companies. The proposed approach derives an efficient graph-based exploration model from defined functional variants. From this, a novel symbolic formulation of multi-variant resource allocation, task binding, and message routing serves as input for a state-of-the-art hybrid optimization technique to derive the individual architecture for each functional variant and the resulting Baukasten at once. For the first time, this enables a concurrent analysis and optimization of individual variants and the Baukasten. Given each manifestation of a component in the Baukasten induces production, storage, and maintenance overhead, we particularly investigate the trade-off between the number of different hardware variants and other established design objectives like monetary cost. We apply the proposed technique to a real-world automotive use case, i. e., a subsystem within the safety domain, to illustrate the advantages of the multi-variant-based design space exploration approach. © 2014 EDAA.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.inform.multiv

Robust Design of E/E Architecture Component Platforms - Graf, Sebastian; Reinhart, Sebastian; Glaß, Michael; Teich, Jürgen; Platte, Daniel (Proceedings of the 52nd ACM/EDAC/IEEE Design Automation Conference (DAC 2015), 2015)

Symbolic Message Routing for Multi-Objective Optimization of Automotive E/E Architecture Component Platforms - Graf, Sebastian; Glaß, Michael; Teich, Jürgen (Proceedings of 18. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2015), 2015)

Timing Analysis of Ethernet AVB-based Automotive E/E Architectures - Reimann, Felix; Graf, Sebastian; Streit, Fabian; Glaß, Michael; Teich, Jürgen (Proc. IEEE International Conference on Emerging Technology & Factory Automation, 2013)
Due to ever-increasing bandwidth requirements of modern automotive applications, Ethernet AVB is becoming a standard high-speed bus in automotive E/E architectures. Since Ethernet AVB is tailored to audio and video entertainment, existing analysis approaches neglect the specific requirements and features of heterogeneous E/E architectures and their applications. This paper presents a timing analysis technique based on Real Time Calculus to consider Ethernet AVB in complex E/E architectures, reflecting key features such as static routing and stream reservation, fixed topology, and real-time applications. A comparison with a simulation on case studies from the automotive domain gives evidence that the proposed technique delivers valuable bounds for complete sensor-to-actuator chains, enabling automatic system synthesis and design space exploration approaches. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.inform.timing

Towards Scalable Symbolic Routing for Multi-Objective Networked Embedded System Design and Optimization - Graf, Sebastian; Reimann, Felix; Glaß, Michael; Teich, Jürgen (Proc. of the International Conference on Hardware/Software Codesign and System Synthesis (CODES+ISSS), 2014)
Symbolic encoding for resource allocation, task binding, and message routing during multi-objective design space exploration (DSE) has gained significant attention in recent years. To determine the message routing, existing symbolic approaches typically rely on an explicit encoding of routing hops which results in a huge number of required variables and/or constraints. As a result, these approaches fail in case of large network diameters and/or a huge number of messages or resources and even for smaller problems, the convergence of the involved optimization process suffers. To tackle this shortcomings, this work proposes three novel symbolic routing encoding strategies that all avoid to encode hops explicitly, but are based on an encoding of individual links or complete sender-receiver paths, but still cover the same design space. The result is a more compact problem representation with less constraints and, in particular, less variables; the latter eliminates ineffective degrees of freedom from the search space and significantly enhances the optimization quality of a multi-objective optimization with even non-linear objectives. In an extensive test-suite, three major classes of wired networked embedded systems are considered: (a) hierarchical stars as in MPSoCs or automotive, (b) redundant backbone buses as common in rail systems or avionics, and (c) mesh-based architectures that often occur in NoC-based MPSoCs. For all three classes, the proposed approaches significantly outperform existing techniques in both scalability and optimization quality and, thus, considerably enlarge the field of application of a multi-objective DSE for the networked embedded system design. Copyright is held by the owner/author(s).
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.inform.toward_5

Unreliable Data Transmissions and Limited Hardware Communication Buffers in Automotive E/E Virtual Prototypes - Graf, Sebastian; Glaß, Michael; Teich, Jürgen (Tagungsunterlagen Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IMMD.inform.unreli